Examination of Banks' Performance and Intellectual Capital in Cambodia: Utilizing FMOLS and DOLS Methods - Ky, Sereyvath; Lim, Siphat (Journal of Ecohumanism, 2024)
In order to address the potential presence of serial correlation and heteroscedasticity in static panel data models such as Pooled Ordinary Least Square (Pooled OLS), Fixed Effect (FE), and Random Effect (RE) models, the study employed Panel Fully Modified Ordinary Least Squares (FMOLS) and Panel Dynamic Ordinary Least Squares (DOLS) methodologies to evaluate the influence of value-added capital and its specific components - human capital, structural capital, and capital employed - on the performance of banks in Cambodia. The results of the research revealed that intellectual capital significantly impacted the return on assets in a positive manner. Specifically, human capital and capital employed were recognized as crucial elements in determining this connection. Both the FMOLS and DOLS estimation techniques produced reliable outcomes, showing positive slope coefficients that were deemed statistically significant at the 1% level. Conversely, the impact of structural capital on bank performance produced diverse results. While the determined slope was considered extremely significant at the 1% level through the FMOLS technique, the findings were inconclusive. More precisely, the projected coefficient showed a positive value when applying the FMOLS approach, but displayed a negative value when using the DOLS method.